Simulation-Based Approaches for Training Communication and Counseling Skills in Clinical Education in Audiology: A Scoping Review - Kanji, Amisha; Watermeyer, Jennifer (American journal of audiology, 2024)
This review article aimed to obtain an understanding of the positive outcomes and challenges associated with the use of simulation-based approaches for teaching communication and counseling skills in clinical education in audiology as described in the literature. A scoping review was conducted during October 2023 to identify published journal articles that described how simulation-based approaches were used for teaching or assessing communication and/or counseling skills among audiology students. Database searches yielded 208 articles initially. Following abstract screening and full-text review, 17 articles were included for analysis. Most studies focused on using simulation-based approaches for teaching, and there was a stronger focus on pediatric audiology. Most studies involved the use of standardized patients, with data collected via quantitative approaches using rating scales and surveys. Simulation-based approaches can offer positive learning experiences and practice opportunities for students acquiring communication and counseling skills. However, the benefits of simulation over traditional methods are unclear. Students may struggle to integrate technical and communication skills in simulated learning experiences. Engaging with simulation-based approaches may provide important practice opportunities, but these methods are not sufficient to ensure acquisition of communication and counseling skills. More qualitative studies are needed to understand the nuances of if and how students might acquire such skills via simulated learning experiences. We offer some suggestions for improvement of future studies on this topic.